A study of atmospheric corrosion indoor and outdoor - Mohd Fahies, Ismail (2009)
Atmospheric corrosion may cause serious damage to metallic structures and equipments. Because of the huge impact of corrosion, it is imperative to have a systematic approach to recognizing and justifying corrosion problems as soon as possible after they become apparent. In this study, the impact of atmospheric corrosion on aluminum, copper and zinc was investigated by exposing the sample in indoor and outdoor atmosphere. Each sample undergoes environmental exposure for 28 days before the surface morphology investigation was conducted. Then the cleaning process follows prior to the final analysis. Scanning Electron Microscope (SEM) was used to study the surface morphology. Corrosion rate was determined for all samples. In indoor environment, it was found that zinc possess the highest corrosion rate; 1.440 mpy while aluminum is the less corrosive sample with only 0.2645 mpy. The outdoor environment investigation yield similar polar of result where the value increase in almost double the result from indoor investigation. Corrosion rate of zinc is 2.103 mpy and the less corrosive sample; aluminum is 0.417 mpy. Any features of corrosion failure give significant clue of the possible corrosion factor. This article details a proven approach to properly determining the effects of the environment and material types to the corrosion rate, and includes surface microstructure of the most common corrosion types, including general corrosion, pitting, and erosion. In conclusion, properties of outdoor and indoor influence the corrosion rate. Indoor environment shield the samples from rain and dew hence decrease the corrosion rate compare to open or outdoor environment where the samples subjected to the dynamicity of weather. Aluminum proves to be the most protective sample and corrosion durable. Hence it may suggest that for both indoor and outdoor application, aluminum is highly recommended.